Underdiagnosis of cervical intraepithelial neoplasia (CIN) 2 orWorse Lesion inWomenwith a Previous Colposcopy-Guided Biopsy Showing CIN 1 - Carlos André Scheler de Souza; Michelle Garcia Discacciati; Maria Gabriela d'Otavianno; Silvia Maria Bergo; Markus Traue; Liliana Aparecida Lucci de Angelo Andrade; Luiz Carlos Zeferino (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective Expectant follow-up for biopsy-proven cervical intraepithelial neoplasia (CIN) 1 is the current recommendation for the management of this lesion. Nevertheless, the performance of the biopsy guided by colposcopy might not be optimal. Therefore, this study aimed to calculate the rate of underdiagnoses of more severe lesions in women with CIN 1 diagnosis and to evaluate whether age, lesion extent and biopsy site are factors associated with diagnostic failure. Methods Eighty women with a diagnosis of CIN 1 obtained by colposcopy-guided biopsy were selected for this study. These women were herein submitted to large loop excision of the transformation zone (LLETZ). The prevalence of lesions more severe than CIN 1 was calculated, and the histological diagnoses of the LLETZ specimens were grouped into two categories: "CIN 1 or less" and "CIN 2 or worse." Results The prevalence of lesions diagnosed as CIN 2 or worse in the LLETZ specimens was of 19% (15/80). Three women revealed CIN 3, and 1 woman revealed a sclerosing adenocarcinoma stage I-a, a rare type of malignant neoplasia of low proliferation, which was not detected by either colposcopy or previous biopsy. The underdiagnosis of CIN 2 was not associated with the women's age, lesion extension and biopsy site. Conclusions The standard methods used for the diagnosis of CIN 1 may underestimate the severity of the true lesion and, therefore, women undergoing expectant management must have an adequate follow-up.